2018
DOI: 10.1016/j.bpj.2017.11.3627
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Evoked Responses in Dorsal Root Ganglion Neurons (DRG) and HEK293 Cells

Abstract: total dimensions of 600 Â 600 Â 100 mm. Pillars of different height with cavities on top, which act as attachment sites for the somata of the neurons, are connected to each other through channels to guide the neurites from one pillar to the next in a precise predefined way. The inner diameter of the channels, 3.6 mm, is tailored to fit the axon-diameter of 2-3 mm. To specifically enhance cell attachment, poly-D-lysin is printed directly into the cavities of the pillars. The substrate is cultured with granule c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, interpretation of the results from in vivo studies can be confounded by indirect effects of US on surrounding muscles, blood vessels and immune cells. In vitro cultures of dissociated sensory neurons from the dorsal root ganglion (DRG) have also been used as a model to study the effects of US neuromodulation ( 67 ). Although the sensory cell somata in the DRG differ significantly from the nerve axons and endings in fundamental electrophysiological properties ( 57 ), the neurite outgrowth in cultured DRG has similar dimensions as axons and nerve endings and thus could potentially be an adequate model for studying peripheral neuromodulation.…”
Section: Peripheral Ultrasonic Neuromodulation – Technical Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, interpretation of the results from in vivo studies can be confounded by indirect effects of US on surrounding muscles, blood vessels and immune cells. In vitro cultures of dissociated sensory neurons from the dorsal root ganglion (DRG) have also been used as a model to study the effects of US neuromodulation ( 67 ). Although the sensory cell somata in the DRG differ significantly from the nerve axons and endings in fundamental electrophysiological properties ( 57 ), the neurite outgrowth in cultured DRG has similar dimensions as axons and nerve endings and thus could potentially be an adequate model for studying peripheral neuromodulation.…”
Section: Peripheral Ultrasonic Neuromodulation – Technical Specificationsmentioning
confidence: 99%
“…To the best of our knowledge, all existing DRG neuromodulations implement electrical stimulation, and the modality of US has yet to be investigated on DRG. A recent pilot report with patch-clamp and calcium imaging recordings on dissociated DRG neurons showed that US evokes action potentials in 33–40% DRG neurons, which may involve the activation of sodium, calcium and non-selective ion channels ( 67 ).…”
Section: Ultrasonic Neuromodulation Of the Peripheral Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation